PENGARUH LITERASI KEUANGAN, PRESEPSI RISIKO, DAN SIKAP KEUANGAN TERHADAP KEPUTUSAN INVESTASI MAHASISWA DI SURAKARTA - Puji Lestari; Rispantyo Rispantyo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This study aims to examine the role of financial literacy, risk perception, and financial attitudes in influencing investment decisions of accounting students at private universities in Surakarta. A quantitative approach was applied by distributing online questionnaires to 88 respondents selected through purposive sampling. The collected data were analyzed using several statistical procedures, including validity and reliability testing, followed by classical assumption tests and multiple linear regression analysis to examine the relationships between variables. The findings reveal that financial literacy does not play a significant role in shaping students’ investment decisions. In contrast, risk perception and financial attitude demonstrate a positive and significant influence. These results suggest that students tend to rely more on their understanding of potential risks and their financial behavior when making investment decisions, rather than solely on their level of financial knowledge